JOINT INFORMATION SYSTEM MODEL APPLIANCE IN MAN-MADE CRISIS MANAGEMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Several crisis communication models can be applied in the discourse of man-made crises occurrence, such as terrorist attacks, cyber-attacks, or explosions caused by negligence and other similar events. However, one of the most comprehensive models in practical terms- and yet one of the least scientifically researched- is the Joint Information System (JIS) model. By nature, the resolution of such critical incidents, which are driven by human intention and action, requires the involvement of multiple actors, primarily state security institutions, as well as non-governmental organizations and possibly others. The JIS model thus provides a collaborative framework for crisis communication, involving multiple stakeholders, including government emergency responders, media representatives, community leaders and other actors depending on the type of incident.  The JIS approach subsequently ensures that critical information dissemination is coordinated, consistent and effective in addressing the needs of all involved parties.  The JIS model is based on five key principles: 1) Integrated communication, which requires collaboration among all stakeholders to ensure a unified message development and delivery, 2) Audience-focused communication, which prioritizes understanding the concerns and informational needs of different audiences to tailor messages accordingly, 3) Timely and accurate communication, which ensures that stakeholders receive reliable and up-to-date information throughout the various crisis phases, 4) Credible communication, which focuses on building trust and maintaining the credibility of information sources and 5) Continuous communication, which highlights the importance of sustained information-sharing in the precrisis stage and  throughout both the crisis management and recovery phases. Recovery from a man-made crisis, including but not limited to terrorist incidents, is a complex and multifaceted process that encompasses physical, emotional, social, and economic dimensions. In the aftermath of such events, effective communication is crucial for maintaining public safety, disseminating critical information and mitigating the psychological and social impacts of the crisis on affected areas and citizens.  This paper examines the application of the JIS model in man-made crisis scenarios, analysing its effectiveness in ensuring structured and transparent communication. The research employs a qualitative analysis of past crisis events where the JIS model has been implemented, drawing insights from case studies and best practices that are available online. The findings indicate that the JIS model significantly enhances crisis response by fostering coordination among stakeholders, reducing misinformation and improving public trust, consequently- maintaining reputational aspects of the state authorities high, that is one of the cornerstones of the successful crisis management. Overall, the JIS model is a highly effective approach to crisis communication, particularly in the context of man-made crises. By adhering to its principles, organizations can enhance their crisis management capabilities, minimize the adverse impacts on affected communities, and facilitate a more efficient recovery process.